Positive fluid balance is associated with increased in-hospital mortality in patients with intracerebral hemorrhage. (28th January 2019) - Shen, Yanfei; Huang, Xinmei; Hu, Yongxia; Zhang, Weimin; Huang, Liquan
ABSTRACT: Objective : This study aimed to investigate the association between fluid balance (FB) and in-hospital mortality in patients with intracerebral hemorrhage (ICH). Methods : Data were extracted from the online database Multi-parameter Intelligent Monitoring in Intensive Care III. Patients were divided into two groups according to the FB status at 48 hours after intensive care unit (ICU) admission: negative and positive 48-hour FB groups. The primary outcome was in-hospital mortality. Results : Data of 1407 patients were analyzed. Linear spline function in logistic models showed significant association between the volume of positive FB and in-hospital mortality (odds ratio (OR) 1.006; 95% CI: 1.002–1.010), while the association between the volume of negative FB and in-hospital mortality was non-significant. For interpretation, FB was further divided into four quartiles. Referred to Q1, the OR of in-hospital mortality stepwise increased from Q2 (OR, 1.11; 95% CI: 0.72–1.68) to Q4 (OR, 1.68; 95% CI: 1.13–2.48). A similar association was also found between FB and Glasgow coma scale at ICU discharge. Conclusions : In patients with ICH, increased volume of positive FB was associated with higher in-hospital mortality while the volume of negative FB was not. Whether maintaining a zero FB status is a beneficial strategy needs further investigation.